Constructing accountability in inter‐organisational collaboration: The implications of a narrow performance‐based focus. Issue 5 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to analyse how accounts of collaboration practice were made and used to construct accountability in the empirical context of coordination associations, a Swedish form of collaboration between four authorities in health and social care. They feature pooled budgets, joint leadership and joint reporting systems, intended to facilitate both collaboration and (shared) accountability.Design/methodology/approach – Empirical data were collected in field observations in local, regional and national settings. In addition, the study is based on analysis of local association documents such as evaluations and annual reports, and analysis of national agency reports.Findings – Accountability is constructed hierarchically with a narrow focus on performance, and horizontal (shared) accountability as well as outcomes are de‐emphasised. Through this narrow construction of accountability the coordination associations are re‐created as hierarchical and accountability is delegated rather than shared.Research limitations/implications – Features such as pooled budgets, joint leadership and joint reporting systems can support collaboration but do not necessarily translate into shared accountability if accountability is interpreted and constructed hierarchically.Practical implications – When practice conforms to what is counted and accounted for, using the hierarchical and narrow construction of accountability, the result may be that the associations become an additional authority. That would increase rather than decrease fragmentation in the field.Originality/value – This research derives from first‐hand observations of actor‐to‐actor episodes complemented with the analysis of documents and reports. It provides critical analysis of the construction and evaluation of accounts and accountability related to practice and performance in collaboration. The main contribution is the finding that despite the conditions intended to facilitate inter‐organisational collaboration and horizontal accountability, the hierarchical accountability persisted. Acknowledgements : The field work in this study was supported financially by Samordningsförbundet Göteborg Hisingen (DELTA). The sponsor had no role in study design; in the collection, analysis and interpretation of data; in the writing of the manuscript; or in the decision to submit the paper for publication. A previous version of this paper was presented in the 8th International Critical Management Studies (CMS) Conference, 10‐12 July, 2013, Manchester, UK. The authors thank the participants of the conference stream Critical Views on Health and Social Care for their feedback.